Humanity biologised: the re-definition of human ethics in Ian McEwan's Enduring Love - Amjad, Fazel Asadi; Seyed Mohammad Marandi; Asli, Amin Pourhossein (Penerbit Universiti Kebangsaan Malaysia, 2018)
The present study investigates how Ian McEwan's Enduring Love (1997) re-defines human ethical qualities within a Darwinian framework. McEwan's Enduring Love from the very beginning to the end abounds in Darwinian images and passages, thereby, it forms a Darwinian lens through which the events of the novel are scanned and interpreted, from the helium balloon gone out of control to a shared happiness resulted from seeing a familiar face at the airport. Within the Darwinian worldview the novel sets, it tries to subvert the traditionally-considered human ethical actions, like heroism, cooperation, courage, and love and therefore redefine them. To prove its claim, this paper, first, explores the Darwinian framework Enduring Love develops, benefiting from the ideas of literary Darwinists and other biopoetical theorists; then, it tries to show how the novel applies the same Darwinian principles to those human ethical qualities mentioned above which results in their redefinition.